Coronavirus Causes Diabetes in People who Did Not Have Diabetes Before They Contracted COVID-19 - Youssef, Ziena; B. Hasan, Bassam (Al-Nahrain Journal of Science, 2022)
Coronavirus disease infects the respiratory system through binding to the receptor of angiotensin-converting enzyme2 (ACE2), Symptoms of the disease develop within 5-6 days after infection, accompanied by mild to moderate symptoms in the initial stage of the disease, and continue for 10-15 days. But it has the potential to develop into severe acute respiratory distress syndrome (ARDS), which leads to the destruction of multiple organs in the body, including the beta cells in the islets of Langerhans in the pancreas, causing type 1 or type 2 diabetes and high blood sugar. The aim of the study is to detect diabetes mellitus in people with COVID-19 who did not have diabetes and did not have a family history of the disease before they were exposed to the virus. COVID-19 was diagnosed by nasal swab through PCR Real-time. The detection of diabetes was through blood tests such as blood sugar, and glycated hemoglobin (HbA1C), and the acute stage of the infection was detected through Dimer, LDH, Ferritin, and C - reactive protein (CRP) tests. From the results that obtained during the research, it was found that the patient percentage with diabetes due to the virus is 20% of type I, while 80% diabetes of type II.